Examining the self-leadership ability of future Guidance and Counselling teachers: which one is better, male-students or female-students ? - Gendon Barus (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2021)
The purpose of this study was to measure the self-leading ability of the future Guidance and Counselling teachers at Sanata Dharma University (USD) Yogyakarta and examine whose self-leadership ability is better, the male-students or the female-students. The subjects of this study were 210 students of study program of Guidance and Counselling USD 2020/2021. The data collection instrument was the Student Self Leadership Ability Scale with a semantic differential model. The data analysis technique applied two methods, namely descriptive category and different test technique t test. The results showed that most of the subjects had achieved a score of self-leadership ability in the high category, but there was no significant difference in the ability of self-leadership in the male-students and the female-students.